2012
DOI: 10.1093/schbul/sbs045
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Hallucinations in Schizophrenia and Nonschizophrenia Populations: A Review and Integrated Model of Cognitive Mechanisms

Abstract: While the majority of cognitive studies on auditory hallucinations (AHs) have been conducted in schizophrenia (SZ), an increasing number of researchers are turning their attention to different clinical and nonclinical populations, often using SZ findings as a model for research. Recent advances derived from SZ studies can therefore be utilized to make substantial progress on AH research in other groups. The objectives of this article were to (1) present an up-to-date review regarding the cognitive mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
279
2
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(300 citation statements)
references
References 48 publications
15
279
2
4
Order By: Relevance
“…Indeed, many of those interviewed report an increased perceived ability to control the occurrence of their voices and-crucially-report that they had not always possessed such an ability, instead developing it over time. Rather than reflecting enhanced executive function and cognitive control, as some have suggested, 8,43,44 this may instead be the result of intentional practice. This, in turn, may result from the lower distress exhibited by the psychics, leading to an increased willingness to engage with and ultimately control them.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many of those interviewed report an increased perceived ability to control the occurrence of their voices and-crucially-report that they had not always possessed such an ability, instead developing it over time. Rather than reflecting enhanced executive function and cognitive control, as some have suggested, 8,43,44 this may instead be the result of intentional practice. This, in turn, may result from the lower distress exhibited by the psychics, leading to an increased willingness to engage with and ultimately control them.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive models propose that auditory hallucinations (AH) occur when an internal mental event is misattributed to an external source (e.g., Bentall, 1990;Waters et al, 2013). It has been suggested that intrusive thoughts may be the mental events that are misattributed to become AH (Morrison, Haddock, & Tarrier, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…W trakcie jednego z dialogów (dialog A) nastąpiła zbieżność między treściami, jakie wypowiadał awatar (treść omamów), a treściami, jakie pacjent słyszał od ojca. W tym momencie nastąpiła zmiana w zakresie monitorowania źródła omamów słuchowych [24] i włączenie treści omamowych do własnych struktur poznawczych. Równocześnie do tego procesu pacjent przeformułował przekonania na temat siły, znaczenia, pochodzenia omamów słuchowych.…”
Section: Komentarzunclassified
“…During one of the dialogues (dialogue A), the words spoke by the avatar (content of hallucinations) were similar to the words spoke to the patient by his father. At this point, there was a change in terms of the monitoring of the source of auditory hallucinations [24] and the inclusion of the content of hallucinations in own cognitive structures. Simultaneously with this process, the patient reformulated his beliefs about the power, meaning and source of auditory hallucinations.…”
Section: Komentarzmentioning
confidence: 99%